A comparative study of the effects of cultural differences on the adoption of mobile learning. (14th April 2014) - Arpaci, Ibrahim
Abstract The objective of this paper is to understand the impact of cultural differences on mobile learning adoption through identifying key adoption characteristics in Canada and Turkey, which have markedly different cultural backgrounds. A multi‐group analysis was employed to test the hypothesised relationships based on the data collected by means of survey questionnaires from 190 and 163 undergraduate students in Turkey and Canada respectively. The results indicated that there is a strong relationship between culture and adoption behaviour, and there are major differences in patterns between the adoption behaviours of the two countries. Implications of these findings are discussed.